Housing and Its Facilities in the Mauritanian City: A Field Study of Boutilimit City (Journal of Libya for geographical studies, 2026)
Since its establishment, the city of Boutilimit has witnessed a gradual urban expansion manifested in the increase of its geographical area. Its urban fabric has shifted from rural housing to solid (permanent) housing through the reconstruction and extension of the original dwelling, although the city’s urban pattern is characterized by a combination of modern housing that responds to the requirements of life and inherited traditional housing that symbolizes the continuity of attachment to the Bedouin environment among groups of nomadic origin. This study aims to analyze the mechanisms controlling the production of the housing function in the city of Boutilimit and to examine their contribution to the multiplicity of housing patterns. It also seeks to reveal the role of local actors in the construction sector in the city, as well as the effectiveness of the city’s urban plan in directing land uses to confront the proposed challenges that affect the organization and development of space. Methodologically, the study is based on the results of a field study, in which diverse methodological tools were employed. Several scientific and practical stages were followed, including a bibliographic study, statistical research, and fieldwork, along with a set of cartographic and statistical techniques.
Keywords: Housing; City; Field Study; Boutilimit